Spiritual Foundations of Socio-Political Activities of Women in Uzbekistan - Makhruya, Khakimova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses legal acts adopted in the republic to ensure the rights and interests of women, strengthen their position in society, and recognize them as important participants in development. It also provides facts about the work done. The protection of women’s rights in our republic, the strengthening of their place in society is reflected in the opportunities provided to them. The decrees and resolutions adopted in this direction are an opportunity for their comprehensive support.